Acid stability of the kinetically stable alkaline serine protease possessing polyproline II fold - Rohamare, Sonali; Javdekar, Vaishali; Dalal, Sayli A.; Nareddy, Pavan Kumar; Swamy, Musti J.; Gaikwad, Sushama M. (Protein Journal, 2015)
The kinetically stable alkaline serine protease from Nocardiopsis sp.; NprotI, possessing polyproline II fold (PPII) was characterized for its pH stability using proteolytic assay, fluorescence and Circular Dichroism (CD) spectroscopy, and Differential Scanning Calorimetry (DSC). NprotI was found to be functionally stable when incubated at pH 1.0, even after 24 h, while after incubation at pH 10.0, drastic loss in the activity was observed. The enzyme showed enhanced activity after incubation at pH 1.0 and 3.0, at higher temperature (50-60 A degrees C). NprotI maintained the overall PPII fold in broad pH range as seen using far UV CD spectroscopy. The PPII fold of NprotI incubated at pH 1.0 remained fairly intact up to 70 A degrees C. Based on the isodichroic point and T-m values revealed by secondary structural transitions, different modes of thermal denaturation at pH 1.0, 5.0 and 10.0 were observed. DSC studies of NprotI incubated at acidic pH (pH 1.0-5.0) showed T-m values in the range of 74-76 A degrees C while significant decrease in T-m (63.8 A degrees C) was observed at pH 10.0. NprotI could be chemically denatured at pH 5.0 (stability pH) only with guanidine thiocynate. NprotI can be classified as type III protein among the three acid denatured states. Acid tolerant and thermostable NprotI can serve as a potential candidate for biotechnological applications.
Keywords: Acid stability; DSC; Kinetic stability; Polyproline fold; Protease; Thermal unfolding

Cloning, expression and in silico studies of a serine protease from a marine actinomycete (Nocardiopsis sp NCIM 5124) - Rohamare, Sonali; Gaikwad, Sushama M.; Jones, Dafydd; Bhavnani, Varsha; Pal, Jayanta; Sharma, Ranu; Chatterjee, Prathit (Process Biochemistry, 2015)
A serine protease (N. protease), from Nocardiopsis sp., was cloned and expressed in Escherichia coli and investigated for its potential kinetic stability. Protein expression using two vectors, pET-22b (+) and pET-39b (+) was compared based on proper folding and soluble expression of the protein. pET-39b (+) was found to be a better vector for soluble expression of this protease containing disulfide bonds. In silico studies were also carried out for N. protease. Homology modeling suggested N. protease to be a member of PA clan of proteases. The phylogenetic analysis showed relatedness of N. protease to kinetically stable proteases. Molecular docking studies performed exhibited interaction of a peptide substrate with catalytic pocket of the enzyme. High temperature MD simulations were performed on N. protease to study its unfolding behavior and comparisons were made with alpha LP. A novel approach to study `cooperativity' of protein unfolding was undertaken, wherein `P' value analysis based on phi and psi values of the protein was performed. Data showed sharper P value transition for alpha LP when compared to N. protease thus indicating relatively less kinetic stability of N. protease. Present study holds significance as the non-streptomycete actinomycetes group is least explored and ensures industrially important enzymes with exceptional stabilities. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Actinomycetes; Cloning and expression; Kinetic stability; Protease; Thermal simulation